Managing adaptive web services using semantic models and automated policy refinement - Carey, Kevin (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2010)
There is an increasing demand for web services to be more flexible, in order to suit fast changing business needs and user requirements. Web services need to be adaptive to changes in context, so as to provide web service personalisation, i.e. services that are adaptive to meet user's preferences or that accommodate to changes in the business environment. This thesis investigates a policy-based management approach to achieving adaptive composite services. A key aspect of policy-based management is to be able to specify high-level policies that can be mapped down to low-level policies, in order to manage the adaptive behaviours of web services. This thesis researches how to describe adaptive composite services so as to expose their adaptive behaviours, and how to specify and automatically refine management policies to dynamically manage these adaptive behaviours.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.